2020
DOI: 10.1186/s12883-020-01768-3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal metastasis of glioblastoma multiforme before gliosarcomatous transformation: a case report

Abstract: Background: Glioblastoma multiforme (GBM) is one of the most aggressive malignant brain tumors. Intracranial GBM metastases to the spine are rarely detected clinically. Secondary gliosarcomas after treatment of primary GBM are rarely described. Case presentation: Herein, we report the case of a 53-year-old woman who presented to our emergency room with progressive headache and weakness on the left side. Plain computed tomography and contrast magnetic resonance imaging of the brain revealed an approximately 6.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…This would be in agreement with the hypothesis that the occurrence of metastases from low-grade gliomas may happen before these tumors undergo grade increase, enabling the ability of tumor cells to settle in metastatic sites [ 3 ]. So far, the treatment of extra-CNS metastasis varies widely and there was no substantial treatment progress over the recent decades [ 20 , 21 ]. In our patient, the locoregional radiotherapy allowed good control of lymph node disease even at a distance of about 8–10 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This would be in agreement with the hypothesis that the occurrence of metastases from low-grade gliomas may happen before these tumors undergo grade increase, enabling the ability of tumor cells to settle in metastatic sites [ 3 ]. So far, the treatment of extra-CNS metastasis varies widely and there was no substantial treatment progress over the recent decades [ 20 , 21 ]. In our patient, the locoregional radiotherapy allowed good control of lymph node disease even at a distance of about 8–10 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IDH-wildtype glioblastoma is the most common primary malignancy and accounts for approximately 45% of all primary malignant brain tumors in adults. Statistically, it is more common in men than in women [16,20,21]. Studies show that in adults, glioblastoma cells can be derived from neural stem and progenitor cells that are located in the subventricular zone, subcortical white matter and the dentate gyrus of the hippocampus [10,18,23].…”
Section: Introductionmentioning
confidence: 99%
“…Gomori's silver staining, reaction with vimentin antibody. Gliosarcoma occurs only in approximately 2% of patients diagnosed with glioma [2,7,8,11,14,16], more often in men than in women, with a ratio of 1.8 : 1. It usually appears in the fourth to sixth decade of life [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…1 MGs are highly proliferative and extensively invade the brain parenchyma, resulting in devastating tumor recurrence and poor prognosis with a median survival of approximately 12-15 months. 2,3 Although the standard treatment primarily involves surgical debulking followed by radiation therapy and possible chemotherapy, [4][5][6] a multidisciplinary approach may be required for MGs to be managed efficiently. In the previous decades, multimodal studies and therapeutic trials have been conducted, but the advances have only extended the median survival rate of patients with MG by a few months.…”
Section: Introductionmentioning
confidence: 99%
“…76 The regimen of administering a chemotherapy agent at a relatively low, minimally toxic dosage for prolonged periods with no extended drug-free interval is called periodic chemotherapy. 77 Using a human melanoma xenograft model, Wedge et al demonstrated that the prolonged administration of O 6 -benzylguanine (O 6 -BG) in combination with TMZ can increase the therapeutic index of TMZ. 35,78,79 However, high drug toxicities and the associated side effects are caused by strategies such as combining different biopharmaceutical agents, increasing the targeted area concentration, and prolonging the treatment.…”
mentioning
confidence: 99%